Supporting the professional sports coach in the workplace: presenting the pedagogue as the "missing scientist" - Williams, S. P.; Bush, A.; Baker, C. (Sports Coaching Review, 2024)
This is a positional paper in which we consider (re)imagining the role of the pedagogue as one who is specifically employed in a multi-disciplinary team of experts that can advise the professional sports coach. Our rationale is underpinned by multiple factors including the low impact of coach education, issues with knowledge translation, and current prevailing discourses in elite sport. Consequently, we employ ethnodrama as a "way in" to explore the precarious existence of elite coaches, cohering specifically around the profligate "hiring and firing" cultures found in professional football. This enables the inquiry to highlight how the pedagogue - the missing scientist - can utilise practical solutions on the ground responding to real-world problems. Going further, we consider how this role could also become a pivotal figure of resistance to the current value system inherent within elite sport reported to jeopardise athletes` health and wellbeing. Thus, we respond to numerous challenges replete in elite sport organisations that are attracting increasing attention.